Hubungan di antara Dimensi Budaya dan Gaya Kepimpinan dengan Tahap Amalan Organisasi Pembelajaran di Universiti Teknologi Mara - Abd Aziz, Noor Azam (2008)
Learning organization is defined as an organization that provides learning environment towards learning, alleviate learning process and develops continuous and collective learning capacity for the betterment of the organization and the society at large. Related studies revealed that organization that practice learning organization will sustain. However, these studies emphasized only the profit-making organizations and few studies were done for educational organizations. Two main factors that contributed to learning organization were leadership and culture. It is therefore the purpose of this study was to examine the relationships between leadership styles and dimensions of culture and the level learning organization practised at UiTM. UiTM is a public university with branches at all states in Malaysia was promoted its status to university in 1999. The UiTM restructuring plan 2001 – 2010 comprised of three phases namely Phase I (Planning), Phase II (Implementation) and Phase III (Evaluation). Learning organization was given priority for implementation phase with special focus to leadership and culture. This quantitative study incorporated three models namely learning organization models by Watkins and Marsick (1996), Bolman and Deal’s (1997) Leadership Frame and Hofstede (1990) Culture Dimensions. This study employed the Dimensions of the Learning Organization Questionnaires (DLOQ) by Watkins and Marsick (1996), Dorfman and Howell Scales (1988) and Bolman and Deal’s Leadership Orientations(Other) questionnaires . The sample of this study was 200 UiTM lecturers and the data collection as well as data analysis was conducted by the researcher. The research findings revealed that UiTM is an educational organization that practice learning organization. Continuous learning scored highest, followed by enquiry and dialogue respectively. The findings positively indicated that UiTM is moving towards learning organization formation. The study also discovered that highest learning occurred at the individual, group and organizational level respectively that indicated UiTM is positively moving towards learning organization. The dominating leadership styles at UiTM are structure, human resource and symbolic. Overall the study discovered a positive relationship between leadership styles and learning organization that lead towards moderate level for each style. As for Culture Dimensions, the highest mean score obtained was collectivism, power distance, masculinity, and uncertainty avoidance respectively. The findings also discovered that a positive relationship between collectivism culture and learning organization. Nevertheless, there was a negative relationship between power distance, uncertainty avoidance and masculinity and learning organization. The findings of this study were expected to be beneficial to other educational organizations as guidance towards formation of learning organization. This study has added to the richness of literature in the related field especially leadership and culture factors.